THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN FORMING CORPORATE REPUTATION AND ITS IMPACT TO MARKET PERFORMANCE OF FIRMS IN INDONESIA - Kurnia, Muhammad Syuchron; Raharja, Surya (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate social responsibility (CSR) disclosure on reputation and reputation and its impact on company market performance. The independent variables in this study are Corporate Social Responsibility (CSR) and Company Reputation. Meanwhile, the company's market performance is a variable depending on its measurement using Tobin's Q. This research refers to research conducted by (Pham & Tran, 2020).The effect of CSR disclosure on market performance mediated by company reputation is considered to have a positive influence by the hypothesis based on stakeholder theory and signal theory. The population in this study are companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The sampling method used in this study was the purposive sampling method with predetermined criteria to produce 50 samples of companies to be studied. The data used are secondary in the form of financial reports and company annual reports obtained through the website www.IDX.co.id and financial information from the Bloomberg terminal. The research was tested using the Structural Equation Model (SEM) approach using Partial Least Square (PLS) software.The results of this study indicate that CSR disclosure in shaping the company's reputation has a negative effect on the company's market performance (Tobin's Q). Then the effect of CSR disclosure on market performance directly also has a significant negative effect on market performance (Tobin's Q). The company's reputation has a positive but significant effect on market performance (Tobin's Q).